“Theory Of Jeo Paradise” In Bhagti And Punjabi Sufi Poetry - Prof. Dr. Nabila Rehman (Migration Letters, 2024)
Punjab has been the cradle of communal social life for centuries. The concept of unity in this social life was brilliantly developed by the Bhagats, Gurus and Sufi sages, which was in stark contrast to the ‘Vern Aashram’ doctrine of Brahmanism. Thus, this thought was not only accepted by the people, but today in this era of globalization, this is the only way that we can make the world a place of peace instead of war and fear, this article has briefly highlighted the thought with examples.